PENGARUH GAYA KEPEMIMPINAN OTORITER, KEDISIPLINAN, DAN LINGKUNGAN KERJA TERHADAP PT. SEPTIAN SUKSES SELALU DI PURWOREJO - INFO NUR WANDAWI (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to analyze (1) the influence of authoritarian leadership style on job performance, (2) the influence of discipline on work performance, (3) the influence of work environment on work performance, and (4) the influence of the three variables together on the performance employees of PT. Septian Sukses Slalu Purworejo. The sample in the study was 47 people. By using sampling technique, data analyze using multiple regression supported by F test and T test and classical assumption test consist of normality test, multicollinearity, and heterokedastisitas. The result of this study indicate that multiple linear regression equation is Y = 34.673 + 0.095 X1 + 0.073 X2 + 0.172 X3. With significant rate 5%. Demonstrates that authoritarian leadership style 0,005 < 0,05 influences work performance. Discipline 0,025< 0,05 which means discipline affect the work performance. Work environment 0,000 < 0,05 which means work environment affect on job performance. Simultaneously, the three variables affect the employee performance of PT. Septian Sukses Slalu Purworejo.